2010
DOI: 10.1016/j.yhbeh.2010.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of obesity by early-life food restriction in genetically hyperphagic male OLETF rats: Peripheral mechanisms

Abstract: The alarming increase in childhood, adolescent and adult obesity has exposed the need for understanding early factors affecting obesity and for treatments that may help prevent or moderate its development. In the present study, we used the OLETF rat model of early-onset hyperphagia induced obesity, which become obese as a result of the absence of CCK1 receptors, to examine the influence of partial food restriction on peripheral adiposity-related parameters during and after chronic and early short term food res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 66 publications
1
12
0
1
Order By: Relevance
“…As in previous studies (Schroeder et al, 2010), the body weight of PF OLETF rats was normalized to that of lean LETO controls, and it was significantly lower than free-fed OLETF from PND 30 and on F(13,143)=148.14, p<0.001; Fig 3B). …”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…As in previous studies (Schroeder et al, 2010), the body weight of PF OLETF rats was normalized to that of lean LETO controls, and it was significantly lower than free-fed OLETF from PND 30 and on F(13,143)=148.14, p<0.001; Fig 3B). …”
Section: Resultssupporting
confidence: 82%
“…This extends the findings of a study by Bi et al (2001) reporting that pair feeding OLETF rats normalized their elevated POMC and decreased NPY mRNA expression in the arcuate nucleus. In addition, other studies found that pair-fed male OLETFs presented normal leptin levels and body fat percentages (Moran and Bi, 2006; Schroeder et al, 2010). Thus we now add that D2R levels were also normalized.…”
Section: Discussionmentioning
confidence: 92%
“…However, the reductions in circulating OT are not necessarily observed across all rodent models of obesity, for reasons that are not entirely clear, as circulating levels in DIO rats and ob/ob mice are, in fact, not decreased relative to their respective lean counterparts [30,62]. In some cases, OT levels are increased in certain obese rat models [95][96][97][98] as well as in obese humans [99] but are reduced following chronic pairfeeding in rats [97] or gastric banding-associated weight loss in humans [99]. In addition, other apparent inconsistencies arise in certain pathological states of energy deficit in humans where it has been shown that nocturnal levels of OT are reduced in both anorexia nervosa [100] and amenorrhea [101].…”
Section: Role Of Ot Signaling In Energy Balancementioning
confidence: 99%
“…However, the mechanisms and pathways underlying central obesity and regulation of body fat distribution are not completely understood. While the genetic risk factors [6] as well as the environmental factors [7,8,9,10] underlying obesity are still relatively poorly understood, a better understanding of the complex interactions between physical, endocrinological, genetic and molecular phenotypes is needed [11]. Recent evidence suggests that only around 50% of the variation between individuals in body weight has a genetic basis, but these effects are dominated by polygenetic environmental interactions that reflect many genetic influences affecting spontaneous physical activity, metabolic rate, endocrinological changes and appetite behavior [1].…”
Section: Introductionmentioning
confidence: 99%